Konsep Ibn Al-‘Arabĭ dan Ranggawarsita Tentang Manusia - Muhammad Luthfi Ubaidillah (Misykah : Jurnal Pemikiran dan Studi Islam, 2020)
Human nature is a study that is always interesting to discuss in various cultures and religions. This paper seeks to present human nature in the view of the great figure of Sufism, namely Ibn al-'Arabi and the great figure of Javanese literature and mysticism, namely Ranggawarsita. In terms of thinking, these two figures have become icons in their world of thought. Ibn al-'Arabî became a pioneer of wujudiah teachings in the world of Sufism. Meanwhile, Ranggawarsita has a mindset that cannot be compared with other poets in the world of Javanese poet thought. Abstrak Hakikat manusia menjadi suatu kajian yang selalu menarik untuk diperbincangkan di berbagai budaya dan agama. Tulisan ini berupaya menyajikan hakikat manusia dalam pandanga tokoh besar tasawuf yaitu Ibn al-‘Arabi dan tokoh besar kesusasteraan dan kebatinan Jawa yaitu Ranggawarsita. Dalam hal pemikiran kedua tokoh ini menjadi ikon dalam dunia kepemikiran mereka. Ibn al-‘Arabî menjadi pelopor ajaran wujudiah dalam dunia sufisme. Sedangkan Ranggawarsita memiliki kepemikiran yang tidak dapat dibandingkan dengan pujangga-pujangga lain dalam dunia pemikiran pujangga Jawa.